Knowledge of Mothers Who Have Babies about Impact Providing Formula Milk in the Village Sihitang Subdistrict Southeastern Padangsidimpuan - Fatimah (PT Inovasi Pratama Internasional, 2023)
Babies who are given formula milk have 14 times the risk of experiencing diarrhea compared to babies who are not given formula milk. A total of 40 cases, 37 infants (92.5%) in the case group suffered from diarrhea and were given formula milk (Astari, 2013). This research was conducted using a descriptive method using a total sampling of 30 respondents, which was examined based on knowledge, age, education, occupation, parity, and information sources. Based on the research results, it is known that the majority of respondents with less knowledge are 18 respondents (60%), the majority of respondents with less knowledge are 20-40 years old (40%). The majority of respondents with less knowledge based on junior high school education were 15 respondents (50%), the majority of respondents with less knowledge of the work of IRT were 11 respondents (36.67%), the majority of respondents with less knowledge based on parity grandepara 9 respondents (30%), the majority of respondents with less knowledge obtained sources of information from electronic media were 10 respondents (33.33%). Based on the results of the study, it can be concluded that the majority of the knowledge of mothers who have babies about the impact of formula feeding is still lacking, so it is hoped that mothers who have babies will follow the counseling so that the mother's knowledge of the impact of formula feeding increases.